Resveratrol preferentially inhibits IgE-dependent PGD2 biosynthesis but enhances TNF production from human skin mast cells - Shirley, Devon; McHale, Cody; Gomez, Gregorio (Biochimica et biophysica acta, 2016)
Resveratrol, a natural polyphenol found in the skin of red grapes, is reported to have anti-inflammatory properties including protective effects against aging. Consequently, Resveratrol is a common nutritional supplement and additive in non-prescription lotions and creams marketed as anti-aging products. Studies in mice and with mouse bone marrow-derived mast cells (BMMCs) have indicated anti-allergic effects of Resveratrol. However, the effects of Resveratrol on human primary mast cells have not been reported. Human mast cells were isolated and purified from normal skin tissue of different donors. The effect of Resveratrol on IgE-dependent release of allergic inflammatory mediators was determined using various immunoassays, Western blotting, and quantitative real-time PCR. Resveratrol at low concentrations (≤10μM) inhibited PGD2 biosynthesis but not degranulation. Accordingly, COX-2 expression was inhibited but phosphorylation of Syk, Akt, p38, and p42/44 (ERKs) remained intact. Surprisingly, TNF production was significantly enhanced with Resveratrol. At a high concentration (100μM), Resveratrol significantly inhibited all parameters analyzed except Syk phosphorylation. Here, we show that Resveratrol at low concentrations exerts its anti-inflammatory properties by preferentially targeting the arachidonic acid pathway. We also demonstrate a previously unrecognized pro-inflammatory effect of Resveratrol — the enhancement of TNF production from human mature mast cells following IgE-dependent activation. These findings suggest that Resveratrol as a therapeutic agent could inhibit PGD2-mediated inflammation but would be ineffective against histamine-mediated allergic reactions. However, Resveratrol could potentially exacerbate or promote allergic inflammation by enhancing IgE-dependent TNF production from mast cells in human skin. •Resveratrol targets the eicosanoid pathway for inhibition in human skin mast cells.•Resveratrol at low concentration inhibits PGD2 biosynthesis but not degranulation.•Resveratrol inhibits FcεRI-induced COX-2 expression but not Syk phosphorylation.•Resveratrol enhances FcεRI-induced TNF production from human skin mast cells.